2019
DOI: 10.1186/s41927-018-0051-6
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and cost-effectiveness of the modified Pilates method versus aerobic exercise in the treatment of patients with fibromyalgia: protocol for a randomized controlled trial

Abstract: Background Fibromyalgia is characterized by chronic generalized pain, fatigue, sleep disorders and other symptoms. Physical exercise is recommended as the first choice of non-pharmacological therapy. Thus, the aim of this study is to evaluate the effectiveness and cost-effectiveness of modified Pilates exercises compared to aerobic exercises in the treatment of patients with fibromyalgia. Methods In this randomized controlled trial with blinded assessor, 98 patients who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…This longitudinal study is a secondary analysis of data from a randomized controlled trial (RCT) on patients with fibromyalgia. 29 In that trial, data were collected at baseline and in three post-treatment periods: eight-week and sixand 12-month follow-ups (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…This longitudinal study is a secondary analysis of data from a randomized controlled trial (RCT) on patients with fibromyalgia. 29 In that trial, data were collected at baseline and in three post-treatment periods: eight-week and sixand 12-month follow-ups (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the RCT protocol were previously published. 29 The aim of the RCT was to evaluate the clinical and costeffectiveness of Pilates compared to aerobic exercises in the treatment of patients with fibromyalgia. In this study, which included 97 randomly assigned patients with fibromyalgia, the main results showed that, except for the EQ-5D at 12month follow-up, there was no difference between Pilates and aerobic exercises for the impact of fibromyalgia and health-related quality of life (HRQoL) at eight-week and six-and 12-month follow-ups.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations